Polymedia Model on the Information-Seeking of Young Urban Indonesian on Fashion and Their Perception on Japanese and Indonesian Brands. - Perbawaningsih, Yudi; Sri Rejeki, MC. Ninik; Tunggal, Immanuel Dwi Asmoro (Department of Communications, Universitas Islam Indonesia, 2022)
In the digital era, urban youth face various media – including conventional media – to seek information related to fashion. Fashion items are one of the top three things Indonesian people buy, and Japanese fashion is one of the foreign brands they can mention. The media and information exposure affect their reaction and response toward the information. This study explored and compared Indonesian urban youth's information-seeking behavior about fashion and their perceptions of Japanese and Indonesian fashion brands. Data were collected through paper and pencil questionnaires administered to 291 students at four educational institutions in two major cities, with a diversity of age, gender, place of residence, religion, and education level. This study suggested that (1) young people used various media (polymedia), both conventional and new media. Digging up information directly to fashion brand outlets was a crucial choice, (2) information-seeking behavior was related to fashion brand perceptions. Perceptions of Japanese brands were better than their Indonesian counterparts, although it varied on different demographic characteristics and diversity of information-seeking patterns. This research has several implications: (1) fashion information must be conveyed to consumers as a unique person rather than as a collective person; (2) fashion information must be delivered either through conventional media – including direct shop visits, as well as new media, (3) Need to build a product as a global brand image.